Revisiting a CAD course in the midst of the global pandemic with an activity-centered framework : Reflections from design students - Gelmez, Koray; Arkan, Selin (FormAkademisk, 2022)
Inevitably, the global pandemic that occurred in 2020 had a significant impact on the practices of design education, and apparently, design teachers were not fully prepared and equipped. In this ambivalent and emergent era, they struggled to adapt their current teaching methods to online education. Since then, various teaching methods have been developed and applied to incorporate online delivery. As we see an invitation to advance learner-centered and process-based teaching approaches regarding Computer-Aided Design (CAD) education in the literature; in this article, we address how a constructively aligned CAD course has been adapted to online learning and how it affected design students’ learning experiences. Hence, we discuss the online CAD learning experience through students’ reflections based on the Activity-Centered Analysis and Design (ACAD) Framework. To get insights into their online learning experience on CAD, we asked students to write their thoughts based on a structured qualitative course evaluation template. Broadly, online learning practices in CAD not only resulted in challenges in design learning but also created opportunities as mentioned in students’ writings. Based on qualitative content analysis, students’ reflections on a CAD class implemented under the context of online learning can include both advantages and disadvantages of the online learning platform, peer learning, peer tutoring, active involvement in the class, communication, etc. As a result, students’ reflections on the CAD course made us think that the dimensions of the ACAD Framework are interwoven and interactive.